Susceptible to Faulty Analysis: United States v. Gaubert and the Resurrection of Federal Sovereign Immunity - Peterson, Bruce A.; Van Der Weide, Mark E. (Notre Dame Law Review, 1996)
Disclaimer: This summary was generated by AI based on the content of the source document.